Employer Related Determinants of Scheme Design in Occupational Defined Contribution Schemes in Kenya - Tari, Justus; Wawire, Nelson W.H.; Ombuki, Charles (My University, 2015)
This paper aims to provide an understanding of employer related determinants of scheme design in occupational defined contribution schemes (ODCS) in Kenya. ODCS involve no promises about the size of the benefits and no risk to the employer. The risk of ending up with low or no benefits falls entirely on the scheme members. It is necessary therefore, that determinants of scheme design are carefully considered in establishment and review of defined contribution schemes to deliver adequate benefits to members. Based on modern portfolio and the life cycle theories, the study investigated the key employer related determinants of scheme design in ODCS in Kenya. Primary data were collected using a questionnaire administered to scheme administrators in the sample. Descriptive statistics were used to profile respondents, describe sample characteristics and a logistic econometric model was applied to evaluate the employer related determinants of scheme design. The study showed that the key employer related determinants of scheme design were the employer’s budgetary constraint and recognition of the length of service of scheme members. From the findings, it was recommended that employers should in addition consider pensionable salary, retirement age and occupation in designing schemes. This would guarantee members a reasonable standard of living after retirement. Keywords: Scheme Design, Occupational Defined Contribution Schemes.
Keywords: Scheme Design